A comprehensive case study of cholecystectomy in a patient with a gallbladder laden with 442 stones - Kedari, Prashant; Joshi, Milind; Kapoor, Vaibhav; Khurana, Sushant (International Surgery Journal, 2024)
Cholelithiasis (gallstones), crystalline formations in the gallbladder, presents a common yet intricate medical concern. These stones can vary in size and composition, ranging from cholesterol to pigment-based stones. Treatment often involves surgical intervention, with laparoscopic procedures being a minimally invasive and effective option. However, complications arise when multiple stones are present, leading to heightened inflammation and recurrent symptoms. In this study, we present a case of a 34-year-old, male who came with complaints of abdominal pain and bloating, intermittent nausea, vomiting, and jaundice for more than 5 days. He was diagnosed with multiple calculi in the gallbladder (acute cholecystitis with cholelithiasis) based on ultrasonography. Since the patient had jaundice, he was suggested to get a magnetic resonance cholangiopancreatography (MRCP) to rule out any pathoanatomy. He received treatment by laparoscopic cholecystectomy and showed improvement within 5 days of surgery.